2016
DOI: 10.5551/jat.34082
|View full text |Cite
|
Sign up to set email alerts
|

Intermedin<sub>1–53</sub> Protects Against Myocardial Fibrosis by Inhibiting Endoplasmic Reticulum Stress and Inflammation Induced by Homocysteine in Apolipoprotein E-Deficient Mice

Abstract: Aim: Endoplasmic reticulum stress (ERS) and inflammation participate in cardiac fibrosis. Importantly, a novel paracrine/autocrine peptide intermedin1–53 (IMD1–53) in the heart inhibits myocardial fibrosis in rats. However, the mechanisms are yet to be fully elucidated.Methods: Myocardial fibrosis in apolipoprotein E-deficient (ApoE -/-) mice and neonatal rat cardiac fibroblasts (CFs) were induced using homocysteine (Hcy).Results: IMD1–53 inhibited myocardial fibrosis in vivo and in vitro. Picrosirius red stai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 54 publications
5
16
0
Order By: Relevance
“…We showed that in calcified-senescent VSMCs, the levels of p-AMPK and p-Akt were downregulated as compared with control, but the level of p-PKA was upregulated. According to the previous studies, the activation of PKA during aging-associated calcification may be a compensatory protective effect [44,45]. Here, we found that inhibitors of all these three signaling factors -PI3K inhibitor LY294002, AMPK inhibitor Compound C and PKA inhibitor H89 efficiently blocked the upregulation of sirt1 by IMD1-53 and thus inhibited the effects of IMD1-53 on calcium deposition and β-galactosidase activity.…”
Section: Discussionsupporting
confidence: 55%
“…We showed that in calcified-senescent VSMCs, the levels of p-AMPK and p-Akt were downregulated as compared with control, but the level of p-PKA was upregulated. According to the previous studies, the activation of PKA during aging-associated calcification may be a compensatory protective effect [44,45]. Here, we found that inhibitors of all these three signaling factors -PI3K inhibitor LY294002, AMPK inhibitor Compound C and PKA inhibitor H89 efficiently blocked the upregulation of sirt1 by IMD1-53 and thus inhibited the effects of IMD1-53 on calcium deposition and β-galactosidase activity.…”
Section: Discussionsupporting
confidence: 55%
“… Saklani et al (2016) suggested that TNF-α is essential for DCM. IL-6, CD68, and MCP-1 are also important factors in cardiac inflammation ( Guo et al, 2016 ; Zhang J.S. et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…After treatment with AS (25, 50, 100 mg/kg/day), pathological changes could be reduced to a certain extent, but the lesion was inevitable in Fig. 3, which showed that AS could protect the myocardium from IR injure [17]. In masson staining, the normal cardiac myocytes were stained red and fibrotic areas were stained blue.…”
Section: Effect Of As On He and Masson Stainingmentioning
confidence: 93%